Front Cover: Intrinsic Dynamic Nature of Neutral Hydrogen Bonds Elucidated with QTAIM Dual Functional Analysis: Role of the Compliance Force Constants and QTAIM‐DFA Parameters in Stability (ChemistryOpen 8/2018). Issue 8 (17th July 2018) - Nishide, Taro; Hayashi, Satoko; Nakanishi, Waro
Abstract : The Front Cover shows Japanese lanterns for the Bon festival dance dangling on two ropes, and several molecular graphs with contour maps for hydrogen bonds (HBs) emerging from the lanterns. The curves of the ropes may correspond to the Δ E (energy of formation) and Cij (compliance constant) values for HBs, for which the product will be constant. More information can be found in the Full Paper by T. Nishide et al onpage 565 in Issue 8, 2018 (DOI:10.1002/open.201800051 ).